Poems in progress drafts from master poets - Ault, Alexandra; Walker, Laura 1986- (British Library Publishing, 2022)
Ask two poets what their first drafts look like, and you'll likely get wildly different answers. From typed pages with delicate annotation to hasty scribbles in a dog-eared notebook, drafts often tell us so much more about poems - and their poets - than the published versions ever could.0Manuscripts range from John Keats' drafts in his own hand, to poems written on toilet paper by Sylvia Pankhurst while confined in Holloway Prison, to early versions typed by Sylvia Plath on the reverse of Ted Hughes' own discarded work. Themed chapters allow for fascinating new comparisons between diverse objects - William Blake's 'London' (1794) sits alongside Andrew Salkey's 'Jamaica' (1973) in discussions of place - revealing how each manuscript has shaped our understanding and practice of poetry today.0Experts from the British Library explain the process and provenance behind poems from the UK and Europe, North America, Asia and the Middle East, highlighting the secrets that published poems often conceal. Practicing poets also reveal their own drafts, with new reflections on writing --
Keywords: Geschichte; Autograf; Lyrik; Englisch; Poetry / History and criticism; Poetics; Poetry / Manuscripts; Poetry / Collections; Authors / Biography; Poésie / Histoire et critique; Poétique; Poésie / Manuscrits; Poésie / Collections; Écrivains / Biographies; Authors; Poetry; Biographies; Collections; Criticism, interpretation, etc; Manuscripts